Barbie’s Existential Awakening: Existential Questions of Identity, Mortality, and Meaning in Greta Gerwig’s Barbie 2023 - Algifary Andhika Putra; Mega Ayu Kristia; Salsa Khoirunissa; Sesilia Seniman Hati Gowasa (STIBA IEC JAKARTA, 2026)
Greta Gerwig’s Barbie (2023) illustrates how popular cinema can act as a platform for philosophical exploration, especially viewed through the perspective of existentialism. Though the movie is well-known for its satirical examination of gender roles and consumer culture, it additionally offers a more profound storyline that explores themes of identity, mortality, and significance. The background of the study lies in the increasing acknowledgment of film as a cultural text capable of refelcting and challenging philosophical issues. The aim is to examine Barbie’s existential turmoil and Ken’s concurrent quest for independence through the lenses of Jean-Paul Sartre, Simone de Beauvoir, Martin Heidegger, and Viktor Frankl. Using a qualitative approach, the study utilizes detailed analysis of important scenes and theoretical triangulation to explore themes of freedom, responsibility, authenticity, and the quest for meaning. The findings reveal that Barbie's encounter with imperfection and mortality represents Heidegger's concept of being-toward-death, whereas her choice to accept humanity signifies Frankl's logotherapy. Ken's reinterpretation of masculinity reinforces Beauvoir's and Sartre's focus on identity shaped by one's own choices. In the end, the research finds that Barbie goes beyond mere entertainment, providing a relatable yet deep examination of existentialist concepts and showcasing the philosophical possibilities of popular film